2017
DOI: 10.1111/jar.12388
|View full text |Cite
|
Sign up to set email alerts
|

Internet and cell phone usage patterns among young adults with intellectual disabilities

Abstract: The framework of support needs of people with disabilities should be considered to promote healthy Internet and cell phone use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 69 publications
7
60
1
8
Order By: Relevance
“…the dimension of access to digital devices is a necessity to access internet and its content. The results of the present study show that adolescents with intellectual disabilities had less access to internet-enabled devices than the reference group, which is in line with the results in earlier research (Jenaro et al, 2017;Palmer et al, 2012). Smartphones were the device that the greatest proportion of adolescents with intellectual disabilities had access to, 67%, though within the reference group nearly all (98%) had access to smartphones.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…the dimension of access to digital devices is a necessity to access internet and its content. The results of the present study show that adolescents with intellectual disabilities had less access to internet-enabled devices than the reference group, which is in line with the results in earlier research (Jenaro et al, 2017;Palmer et al, 2012). Smartphones were the device that the greatest proportion of adolescents with intellectual disabilities had access to, 67%, though within the reference group nearly all (98%) had access to smartphones.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning access to smartphones the present study found that 67% of the participants with intellectual disabilities had access to smartphones. These numbers are contrary to the ones in the study from Palmer (2012), where only 20% of participants with intellectual disabilities had access to mobile phones, but equivalent to more recent research from Spain (Jenaro et al, 2017) with 73% participants with intellectual disabilities having access to smartphones. This is an example of the vast development of internet-enabled devices and its accessibility even to young people with intellectual disabilities in the five years separating the two studies.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Whether risk is associated with particular technology usage patterns has not been adequately explored. However, Jenaro et al, (2017) found that young people with ID were significantly more likely to have moderate to severe mobile phone (19.4% vs. 8.0%) and Internet addiction (27.3% vs. 7.8%), based on DSM-V criteria, than typically developing peers. Whether these criteria represent pathology or the normal range of use for a group that tends to be socially disadvantaged or excluded is debatable.…”
Section: Experiences and Awareness Of Riskmentioning
confidence: 92%